2021
DOI: 10.1016/j.aquaculture.2020.735830
|View full text |Cite
|
Sign up to set email alerts
|

Crowding reshapes the mucosal but not the systemic response repertoires of Atlantic salmon to peracetic acid

Abstract: Knowledge of the impact of aquaculture chemotherapeutants on fish physiology is scarce. This is particularly relevant for peracetic acid (PAA), a widely used oxidative disinfectant in aquaculture. The chemical behaviour in water is well studied but knowledge about the physiological consequences for fish is limited. The present study investigated the transcriptomics, morphology, and physiology of Atlantic salmon (Salmo salar) responses to PAA and explored how crowding prior to exposure influenced these response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 45 publications
3
36
1
Order By: Relevance
“…Besides the activation of several effector molecules that provide an interconnected response to oxidant-triggered oxidative stress, it is compelling to observe that several genes for molecules for cytostructural and extracellular matrix were represented in the list of upregulated genes. Previous studies using this oxidant found histostructural changes, though minimal, in the gill and skin mucosa [4,27,42]. We can speculate that the upregulation observed here may play a role in maintaining the structural integrity and barrier functionality under oxidative challenge.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Besides the activation of several effector molecules that provide an interconnected response to oxidant-triggered oxidative stress, it is compelling to observe that several genes for molecules for cytostructural and extracellular matrix were represented in the list of upregulated genes. Previous studies using this oxidant found histostructural changes, though minimal, in the gill and skin mucosa [4,27,42]. We can speculate that the upregulation observed here may play a role in maintaining the structural integrity and barrier functionality under oxidative challenge.…”
Section: Discussionsupporting
confidence: 57%
“…Thereafter, the oxidant (Divosan Forte™, Lilleborg AS, Olso, Norway) was added to the water column to achieve a final concentration of 10 ppm. This concentration was 2x higher than the concentration we earlier tested and reported [4]. Aeration was supplied to enable mixing and to maintain the oxygen level.…”
Section: Oxidant Exposure Experimentsmentioning
confidence: 82%
See 3 more Smart Citations